HUBUNGAN KELAHIRAN BAYI KEMBAR DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) DI RUMAH SAKIT UMUM PUSAT Dr. MOHAMMAD HOESIN PALEMBANG TAHUN 2010 - DESI ANDRIANA DESI ANDRIANA (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2012)
Low birth Weight is defined as babies born weighting less than 2500 grams. Incidence of LBW in the General Hospital Dr Center. Mohammad Hoesin Palembang in 2009 amounted to 313 cases from 2,400 the number of babies born. The purpose of this study was to determine the relationship of independent variables (multiple births) with the dependent variable (incidence of LBW). This study uses survey methods using analytic approach Sectional Cross. The study population was all infants born at General Hospital Dr Center. Mohammad Hoesin Palembang in 2010, amounting to 2439 and sampled 343 respondents. Random sampling method is by way of a simple random (Simple Random Sampling). From univarat analysis performed on 343 infants born to be obtained according to the birth of twins, a larger single baby that is 302 respondents (88%) compared with the birth of twins by 41 respondents (12%). Statistical test results showed the birth of twins to have a meaningful relationship with the incidence of low birth weight (p value = 0.000). It is recommended for health workers (midwives) hospitals should increase outreach activities with communities, especially in the mother in order to understand when to start during pregnancy and terminating the pregnancy and how to consume good nutrition to reduce the incidence of LBW and examination of twin births in order to maintain the health of infants and mothers